Obervation of Thymus Regression Time of ALPU chicken - Kamiliyatul Fadhilah; Erina Erina; M Aman Yaman (Universitas Syiah Kuala, 2022)
This study aimed to determine the number of lobes and thymus regression time of ALPU chickens. The samples were 76 ALPU chickens aged 1 – 19 weeks, consisted of 38 male and 38 female chickens. Two male and 2 female chickens were sacrificed every week and the thymus were collected and weighed. The results showed that the increase in thymus weight occurred in the age range of 1 – 15 weeks and reached the maximum weight at the age of 15 weeks. Thymus was decreased in weight at the age of 16 – 17 weeks. Thymus regressesion occurred at the age of 18-19 weeks. The thymus had 5-9 lobes. The result of T test on the average weight of ALPU chicken thymus showed that the weight of male ALPU chicken thymus of starter phase compared with grower phase was significantly different (p0.05), while the grower phase with finisher phase was not significant or there was no difference (p0,05). The result of T-test for weight of female ALPU thymus showed that the weight of thymus of starter phase compared to grower phase chickens was significantly different (p0.05), whereas grower phase with finisher result was not significantly difference (p0.05).Therefore, it was concluded that the number of thymus lobes of ALPU chickens are 5 - 9 lobes and the time of thymus regression of ALPU chicken occurs at the age of 18 - 19 weeks.